The effects of the antecedent use of inhaled steroid on the clinical course of COVID-19: A retrospective study of asthmatic patients - Yousif S. Alakeel; Ebtihal F. Alharbi; Haifa A. Alhaidal; Aisha M. Jumaa; Latifah K. Albaiahy; Noura S. Alsagami; Shatha A. Alshahrani (Elsevier, 2022)
Background: There is conflicting evidence regarding the effect of asthma and its different therapeutic options on COVID-19 severity and the clinical outcomes. Aim: This study aimed to investigate the relationship between using inhaled corticosteroids (ICS) by asthmatic patients and the severity of COVID-19. Materials and methods: This retrospective observational study was conducted from March 15 to October 23, 2020 and included data of all COVID-19 asthmatic patients (n = 287) at King Abdulaziz Medical City. Twelve patients were excluded due to poor medication history documentation or using ICS for non-asthma indication. Ordinal logistic regression was used to determine the clinical variables that affect COVID-19 severity. The clinical outcomes of ICS and non-ICS users were compared. Results: Of the sample (n = 275), 198 (72%) were using ICS therapy. No significant difference was found between ICS and non-ICS users in disease severity (P = 0.12), mortality (P = 0.45), ICU admission (P = 0.78), and the occurrence of complications. However, the number of days on ventilation were significantly increased in ICS users (P = 0.006). Being prescribed the ICS/LABA combination (adj OR: 0.72 [0.15,1.2]; P = 0.021), being hypertensive (adj OR: 0.98 [0.28,1.6]; P = 0.006), having cancer (adj OR: 1.49 [0.12, 2.8]; P = 0.033), or having diabetes (adj OR: 0.75 [0.09, 1.4]; P = 0.024) could not increase the risk for more severe disease. Conclusion: Overall, ICS therapy did not alter the COVID-19 severity or mortality in asthmatic patients. The continued use of ICS during the pandemic should be encouraged to prevent asthma exacerbations.